RG100204, A Novel Aquaporin-9 Inhibitor, Reduces Septic Cardiomyopathy and Multiple Organ Failure in Murine Sepsis - Mohammad, Shireen; O’Riordan, Caroline E.; Verra, Chiara; Aimaretti, Eleonora; Alves, Gustavo Ferreira; Dreisch, Klaus; Evenäs, Johan; Gena, Patrizia; Tesse, Angela; Rützler, Michael; Collino, Massimo; Calamita, Giuseppe; et al. (Frontiers in Immunology, 2022)
Sepsis is caused by systemic infection and is a major health concern as it is the primary cause of death from infection. It is the leading cause of mortality worldwide and there are no specific effective treatments for sepsis. Gene deletion of the neutral solute channel normalizes oxidative stress and improves survival in a bacterial endotoxin induced mouse model of sepsis. In this study we described the initial characterization and effects of a novel small molecule AQP9 inhibitor, RG100204, in a cecal ligation and puncture (CLP) induced model of polymicrobial infection. In vitro, RG100204 blocked mouseAQP9 H2O2 permeability in an ectopic CHO cell expression system and abolished the LPS induced increase in superoxide anion and nitric oxide in FaO hepatoma cells. Pre-treatment of CLP-mice with RG100204 (25 mg/kg p.o. before CLP and then again at 8 h after CLP) attenuated the hypothermia, cardiac dysfunction (systolic and diastolic), renal dysfunction and hepatocellular injury caused by CLP-induced sepsis. Post-treatment of CLP-mice with RG100204 also attenuated the cardiac dysfunction (systolic and diastolic), the renal dysfunction caused by CLP-induced sepsis, but did not significantly reduce the liver injury or hypothermia. The most striking finding was that oral administration of RG100204 as late as 3 h after the onset of polymicrobial sepsis attenuated the cardiac and renal dysfunction caused by severe sepsis. Immunoblot quantification demonstrated that RG100204 reduced activation of the NLRP3 inflammasome pathway. Moreover, myeloperoxidase activity in RG100204 treated lung tissue was reduced. Together these results indicate that AQP9 may be a novel drug target in polymicrobial sepsis.